2020
DOI: 10.1002/cbdv.201900462
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cytotoxicity and Antimicrobial Evaluation of New Coumarin‐Tagged β‐Lactam Triazole Hybrid

Abstract: A series of coumarin-tagged β-lactam triazole hybrids (10a -10o) were synthesized and tested for their cytotoxic activity against MDA-MB-231 (triple negative breast cancer), MCF-7 (estrogen receptor positive breast cancer (ER +)) and A549 (human lung carcinoma) cancer cell lines including one normal cell line, HEK-293 (human embryonic kidney). Two compounds 10b and 10d exhibited substantial cytotoxic effect against MCF-7 cancer cell lines with IC 50 values of 53.55 and 58.62 μM, respectively. More importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…[46] Incorporation of isatin into the 1,2,3-triazole-tethered coumarin hybrid (30) showed cytotoxicity, with an IC 50 value of 18.67 μM against A549 cells. [47,48] 1,2,3-Triazole-incorporated asiatic acid derivative 31 was found to be active, with IC 50 values in the range 2.67-4.84 μM against the three tested lung cancer cells. Moreover, this compound was nontoxic toward normal HL-7702 cells and the NF-κB inhibitor, and induced apoptosis and suppressed cell migration.…”
mentioning
confidence: 99%
“…[46] Incorporation of isatin into the 1,2,3-triazole-tethered coumarin hybrid (30) showed cytotoxicity, with an IC 50 value of 18.67 μM against A549 cells. [47,48] 1,2,3-Triazole-incorporated asiatic acid derivative 31 was found to be active, with IC 50 values in the range 2.67-4.84 μM against the three tested lung cancer cells. Moreover, this compound was nontoxic toward normal HL-7702 cells and the NF-κB inhibitor, and induced apoptosis and suppressed cell migration.…”
mentioning
confidence: 99%
“…Ma et al synthesized a new series of 1,2,3-triazole-pyrimidine-urea derivatives and evaluated their anti-proliferative activity against selected four different human tumour cell lines including MCF-7, MGC-803, EC-109, and B16-F10. The compounds 43a–43c exhibited significant growth inhibition against B16-F10 with IC 50 values of 32 μM, 35 μM, and 42 μM among all the tested compounds [ 72 ]. …”
Section: Main Textmentioning
confidence: 99%
“…Compound 28b also showed inhibition against P . aeruginosa (% inhibition = 18.97), while compound 28d inhibited C. albicans (%inhibition = 21.65) class pathogens (Dhawan et al, 2020).…”
Section: Biologically Active 123‐triazole‐o‐heterocycle Hybridsmentioning
confidence: 99%
“…their anti-malarial activity and found that compounds 28b and 28d were the most eminent members of the series. Compound 28b also showed inhibition against P. aeruginosa (% inhibition = 18.97), while compound 28d inhibited C. albicans (%inhibition = 21.65) class pathogens (Dhawan et al, 2020). Lipeeva and associates reported the synthesis of some novel triazole-coumarin hybrids and tested for their in vitro anti-bacterial activity against several pathogens.…”
Section: Triazole-coumarin Hybridsmentioning
confidence: 99%